Quantitative Methods for Business - Waters Donald (Addison-Wesley Publishing Company, 1994)
This book provides complete topic coverage for a first course in Quantitative methods, concentrating on methods which have proved useful in practice. It assumes no previous knowledge of either Management or Quantitative Methods. Preface, Background to Quantitative Methods, Numbers and Managers, Tools for Quantitative Methods, Data Collection and Description, Collecting Data, Using Diagrams to Present Data, Using Numbers to Describe Data, Describing Changes with Index Numbers, Solving Business Problems, Calculations with Money, Relating Variables by Regression, Business Forecasting, Using Matrices to Solve Equations, Planning with Linear Programming, Using Calculus to Describe Changes, Business Statistics, Uncertainty and Probabilities, Probability Distributions, Using Samples in Business, Testing Hypotheses, Analyzing Business Decisions, Controlling stocks, Planning Projects with Networks, Queues and Simulation, Appendices, Index.